The devil's foot [anglicky] - Doyle, Arthur Conan Sir 1859-1930; Bellucci, Arianna (Illustrator); Baudet, Stephanie, 1945- (Leicester : Sweet Cherry Publishing, 2021)
You should write about the case of the Devil´s Foot. I am sure your readers would love to hear about the day we almost DIED.
Includes QR code to access audiobook.
Formerly CIP.
Keywords: Holmes, Sherlock -- Juvenile fiction; Watson, John H. -- (Fictitious character) -- Juvenile fiction; Detective and mystery stories; Children's stories; detektívky, trilery; cudzojazyčná literatúra; čítam si sám (7+)